2021
DOI: 10.3390/nitrogen2030022
|View full text |Cite
|
Sign up to set email alerts
|

Poultry Manure Induced Garden Eggs Yield and Soil Fertility in Tropical and Semi-Arid Sandy-Loam Soils

Abstract: Synthetic nitrogen fertilizer use comes with unsustainable financial and environmental costs, making it not attractive to small-scale and organic farmers. Poultry manure (PM) when available is a primary fertilizer source for small-scale and organic farmers but there is still limited research on its effects of specific crops and soil fertility under specific practices. The study investigated PM effects on garden egg in three seasons in Ghana and PM effects soil fertility in sandy-loam soils of Arizona after thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…The favorable results of poultry manure on improved sweet potato yield reported in this study could be due to the mineral nutrient supply from the poultry manure (Table 2). Similar results on higher crop yields have been reported in previous studies (Adekiya and Agbede, 2017;Adeyemo et al, 2019;Hoover et al, 2019;Mpanga et al, 2021). In a similar study with tomatoes, compost with poultry manure substantially enhanced both biomass and shoot nitrogen content when compared to a control that received no fertilizer (Mpanga et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The favorable results of poultry manure on improved sweet potato yield reported in this study could be due to the mineral nutrient supply from the poultry manure (Table 2). Similar results on higher crop yields have been reported in previous studies (Adekiya and Agbede, 2017;Adeyemo et al, 2019;Hoover et al, 2019;Mpanga et al, 2021). In a similar study with tomatoes, compost with poultry manure substantially enhanced both biomass and shoot nitrogen content when compared to a control that received no fertilizer (Mpanga et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Many factors impact these benefits, including increased soil pH due to high cations like calcium in poultry manure, increased organic matter content, and increased microbial activities that slowly release sparingly soluble minerals in poultry manure for plant uptake. The slow release of nutrients from poultry manure allows nutrients availability to the plant throughout the life cycle than the readily available chemical fertilizers, which is prone to leaching during heavy rains (Mpanga et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil for the greenhouse study (Table S1a) was sampled at a depth of 0–15 cm from the University of Arizona Experiment Station at Cornville, Arizona pasture field 2 weeks after annual manure application. The field had annual poultry manure applications as the standard FP at 2239.5 kg ha –1 year −1 , which was split‐applied (1:1) in March and September (Table S1a; Mpanga et al., 2021). The soil was air‐dried in the greenhouse and passed through a 2‐mm sieve to remove stones and large plant materials and mixed uniformly.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have been carried out recently to overcome the sandy land problems mentioned above. The researchers [9][10][11] concluded that inputting organic matter into sandy soils would improve soil quality, ultimately improving the growth performance and productivity of the evaluated plants. Furthermore, to overcome the low nutrient retention in sandy soil, [12,13] concluded that input of organic material in the form of slow release in biochar is beneficial if applied to sandy soil.…”
Section: Introductionmentioning
confidence: 99%